Estudo clínico piloto do efeito de membranas de gelatina contendo ácido úsnico incorporado em lipossomas no processo de cicatrização de queimaduras - Costa, Aida Carla Santana de Melo (2017)
Burns provoke a metabolic impairment with systemic repercussions, leading to need for products that act directly on burns healing, such as usnic acid, observed in previous studies in rodent and swine models. For this, gelatine has been widely used in biomaterials, allowing drugs incorporation. In this perspective, the objective of this research was to evaluate the effect of gelatine membranes (P1QLS08) containing usnic acid incorporated in liposomes on the healing process of second degree burns in humans. It is a Pilot Clinical Trial, controlled and randomized, developed at Burns Treatment Unit of Sergipe Emergency Hospital. Thirty individuals were studied, the patient being his own control. The areas for analysis were randomly selected, comprising a test region (P1QLS08 membrane) and a control region (treated with silver sulfadiazine - SDZ, reference product). The patients were submitted to anamnesis and were followed for 7, 14 and 21 days after administration of the products. At determined times, standardized photographic records were made of P1QLS08 and SDZ areas, as well as wound secretion collection through the swab. Then, a microbiological analysis was performed, a macroscopic description of each image, as well as the analysis by Image J®, in order to obtain a quantitative evaluation. It was observed Pseudomonas aeruginosa and Acinetobacter baumanni prevalence, followed by Staphylococcus aureus in both groups. A better clinical aspect of the lesions was observed, with a pattern of area reduction visibly better in P1QLS08 than SDZ, besides lower relief, nearer to normal vascularization, less pigmentation and flexibility more compatible with physiological condition in P1QLS08 group when compared to SDZ group (p <0.05), effectively contributing to development and use of a new product for clinical importance in biological events acceleration associated with the dynamic of cicatricial repair in burn patients. This thesis also had two systematic reviews, one for patents and the other for clinical evaluation instruments in burn patients.